Effect of Bixa orellana (achiote) leaves aquous and hydroetanolic extracts on non-enzymatic indicators of paracetamol hepatoxicity in rats - Huamán, Oscar (2013)
Objectives: To determine the effect of Bixa orellana leaves aqueous and hydroethanolic extracts on non-enzymatic indicators ofhepatotoxicity in rats subjected to acetaminophen. Design: Experimental. Setting: Research Center of Biochemistry and Nutrition,Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Thirty-five male rats aged 3 months. Interventions: Rats wererandomized into 5 groups that received orally and for 10 days: positive and negative controls NaCl 0.9%, silymarin 300 mg/kg, aqueousextract 500 mg/kg and hydroethanolic extract 500 mg/kg; after fasting 24 hours, paracetamol 400 mg/kg peroral was administered atthe fifth day, except for the negative control. Under ether anesthesia cardiac puncture was performed to obtain blood. Main outcomemeasures: Liver ratio (liver weight/animal weight x 100), total bilirubin (TB), direct (BD) and indirect (BI) bilirubin, hepatomegaly,thiobarbituric acid reactive species (TBARS) in liver and serum. Results: Treatment with aqueous extract alone decreased the followingindicators: BT and BI (p<0.01), serum TBARS (p<0.05), hepatomegaly -13.2% (p<0.01). The group receiving hydroethanolic extractreduced BT, BI (p<0.01), BD (p<0.05), TBARS in liver (p<0.01), hepatomegaly -9.37%. Conclusions: Bixa orellana (achiote) leavesaqueous and hydroethanolic extracts showed hepatoprotective effect against paracetamol in toxic doses in rats.